Pengaruh Return On Equity (ROE) Dan Debt To Equity Ratio (DER) Terhadap Price To Book Value (PBV - D. Muhammad Yamin (Universitas La Tansa Mashiro, 2022)
This research is motivated by the importance of Price to Book Value (PBV) which is a ratio in seeing the value of a company so that goals can be realized properly. This study aims to determine the effect of Return On Equity and Debt to Equity Ratio on Price to Book Value in Manufacturing Companies (Food and Beverage Sub Sector) Listed on the Indonesia Stock Exchange for the 2017-2021 period. This research uses quantitative methods. The population in this study amounted to 39 companies. After selecting the sample using the purposive sampling technique, 12 companies were sampled. Normality Test, Heteroscedasticity Test, Multicollinearity Test, and Autocorrelation Test. The hypothesis testing used in the study includes: Multiple linear regression analysis, Correlation analysis, Analysis of the coefficient of determination, t test, and F test.